Contrapuntal Echoes in Night Sky with Exit Wounds: A Critical Reading of Ocean Vuong’s Poetry through Edward Said’s Lens - Awais Yousaf; Amna Yousaf; Sundas Khan (Indus Journal of Social Sciences, 2025)
Ocean Vuong’s Night Sky with Exit Wounds (2016) is a poignant collection that bridges personal experience with broader historical and cultural contexts, particularly those of war, migration, and queerness. This paper employs Edward Said’s concept of contrapuntal reading to critically analyze Vuong's poetry, exploring how Vuong’s personal narratives of exile, trauma, and identity intersect with global histories of war, imperialism, and cultural displacement. Contrapuntal reading encourages readers to acknowledge the intertwined nature of personal and political histories, amplifying marginalized voices in the process. This paper argues that Vuong’s poetry presents a counter-history to the dominant narratives of the Vietnam War and immigration, offering a nuanced perspective that complicates traditional views of national identity, memory, and belonging. The analysis will focus on how Vuong’s poetic language resists hegemonic structures of power, particularly through his exploration of language, queerness, and the legacy of war.